Mechanistic study on the bis(p-sulfonatophenyl)phenylphosphine synthesis of monometallic Pt hollow nanoboxes using Ag*-Pt core-shell nanocubes as sacrificial templates - Tan, Y.-N. (2014)
10.1021/jp0741049